Kebijakan Utang dan Investasi Terhadap Pembangunan Ekonomi Islam - Ahmad Muaffi Ahdi; Ahmad Muzaqi Mu’min (Islamic Economics and Business Review, 2022)
The purpose of this study is to examine debt and investment policies towards Islamic economic development. In this study, the author used a descriptive research method which explains in sequence debt and investment policies in Islamic economic development. Meanwhile, to analyze data using content analysis, which is a method used to make conclusions from a text. The results of this study show that debt can be a support for economic development. But the debt is the last alternative used.